2022
DOI: 10.3389/fevo.2021.808430
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Secretome Analyses of Trichoderma/Arabidopsis Co-cultures Identify Proteins for Salt Stress, Plant Growth Promotion, and Root Colonization

Abstract: Numerous Trichoderma strains are beneficial for plants, promote their growth, and confer stress tolerance. A recently described novel Trichoderma strain strongly promotes the growth of Arabidopsis thaliana seedlings on media with 50 mM NaCl, while 150 mM NaCl strongly stimulated root colonization and induced salt-stress tolerance in the host without growth promotion. To understand the dynamics of plant-fungus interaction, we examined the secretome from both sides and revealed a substantial change under differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…tritici [83], for example, and several CFEM domain-containing proteins were found in the secretome of Trichoderma spp. in cocultivation with A. thaliana [84]. In our previous work, we found that tacfem1 was upregulated when confronted with the phytopathogen R. solani anastomosis group AG5 during contact and overgrowth of the pathogen, but not when confronted with the anastomosis group AG2, and it was upregulated in the interaction with A. thaliana on days 5 th and 7 th days [23], however, there is little information on CFEM proteins from Trichoderma spp.…”
Section: Discussionmentioning
confidence: 90%
“…tritici [83], for example, and several CFEM domain-containing proteins were found in the secretome of Trichoderma spp. in cocultivation with A. thaliana [84]. In our previous work, we found that tacfem1 was upregulated when confronted with the phytopathogen R. solani anastomosis group AG5 during contact and overgrowth of the pathogen, but not when confronted with the anastomosis group AG2, and it was upregulated in the interaction with A. thaliana on days 5 th and 7 th days [23], however, there is little information on CFEM proteins from Trichoderma spp.…”
Section: Discussionmentioning
confidence: 90%
“…It can be hypothesized that the interaction of the two strains with the hemp plant, in terms of level of colonization, types of activated pathways and magnitude of the responses triggered in the host plant, may vary according to the environmental conditions. In this regard, evidence has been reported that plant exposure to salinity strongly increased the root colonization by Trichoderma strains and induced stress tolerance in Arabidopsis plants [37], and that seed inoculation with the T-22 strain in certain crops gave greater benefits under stress than under optimal growth conditions [38]. As for the mechanisms activated by the fungus, evidence exists that Trichoderma spp.…”
Section: Hemp Plant Growth and Root Morphology And Their Modulation B...mentioning
confidence: 99%
“…In addition, under stressed conditions, WSC domain proteins, viz., FGB1 and WSC3, may be involved in b-glucan remodeling in the fungal cell wall (Wawra et al, 2019). A comparative secretome analysis of Trichoderma under salt stress conditions revealed that, in the presence of its plant host, the expression of WSC domain proteins in Trichoderma decreases, which may be indicative of the benefits derived by the fungus from its symbiont (i.e., the plant) through intensified root colonization (Rouina et al, 2022).…”
Section: Wall Stress Responsive-component Domain Proteinmentioning
confidence: 99%